2021
DOI: 10.1021/acsbiomaterials.1c00913
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin/Poly(vinyl Alcohol) Microneedles as Carriers for the Delivery of Singlet Oxygen Photosensitizers

Abstract: Photodynamic therapy (PDT) is a medical treatment in which a combination of a photosensitizing drug and visible light produces highly cytotoxic reactive oxygen species (ROS) that leads to cell death. One of the main drawbacks of PDT for topical treatments is the limited skin penetration of some photosensitizers commonly used in this therapy. In this study, we propose the use of polymeric microneedles (MNs) prepared from silk fibroin and poly(vinyl alcohol) (PVA) to increase the penetration efficiency of porphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Through the quantitative statistics of cell viability, we found that SFMA did have a certain decrease effect on the viability of HaCaT, but there was no cytotoxicity (96% viability percentages). Ulloa Rojas et al proved that HaCaT cells cultured with SF/PVA microneedles presented above 75% viability percentages, which are potential low-toxic materials for biomedical use . In this research, we found that the modified SFMA/PVA hydrogel microneedles were non-cytotoxic to HaCaT cells, but the major problem of irritation and skin sensitization need to be examined in our future studies.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Through the quantitative statistics of cell viability, we found that SFMA did have a certain decrease effect on the viability of HaCaT, but there was no cytotoxicity (96% viability percentages). Ulloa Rojas et al proved that HaCaT cells cultured with SF/PVA microneedles presented above 75% viability percentages, which are potential low-toxic materials for biomedical use . In this research, we found that the modified SFMA/PVA hydrogel microneedles were non-cytotoxic to HaCaT cells, but the major problem of irritation and skin sensitization need to be examined in our future studies.…”
Section: Resultsmentioning
confidence: 51%
“…Ulloa Rojas et al proved that HaCaT cells cultured with SF/PVA microneedles presented above 75% viability percentages, which are potential low-toxic materials for biomedical use. 28 In this research, we found that the modified SFMA/PVA hydrogel microneedles were noncytotoxic to HaCaT cells, but the major problem of irritation and skin sensitization need to be examined in our future studies. The addition of α-MSH could promote the proliferation of HaCaT cells (Figure 4B).…”
Section: In Vitro Biocompatibility and Functionalmentioning
confidence: 82%
“…Tuning the β-sheet range using methanol vapor annealing can aid in rapid and sustained drug release [ 28 , 31 , 32 ]. Rojas et al [ 33 ] blended PVA with SF to prepare polymer MNs, which can improve the transdermal delivery of porphyrins. Yin et al [ 34 ] developed an SF MNs drug delivery system with different small molecule reagents, with a tremendous transdermal drug release effect and little dissolution loss.…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been made to enhance either the biodegradability or the physical properties of PVA matrix by the incorporation of bio‐based reinforcement materials (i.e., silk fibroin, 9 chitosan, 10 lignin, 11 and cellulose, 12 etc.). Among these bio‐based reinforcement materials, lignin is one of most abundant, cost‐effective, and biodegradable polymers on the earth.…”
Section: Introductionmentioning
confidence: 99%